Overcoming the triad of rural health disparities: How local culture, lack of economic opportunity, and geographic location instigate health disparities. (May 2014) - Thomas, Tami L; DiClemente, Ralph; Snell, Samuel
Objective: To discuss how the effects of culture, economy, and geographical location intersect to form a gestalt triad determining health-related disparities in rural areas. Methods: We critically profile each component of the deterministic triad in shaping current health-related disparities in rural areas; evaluate the uniquely composed intersections of these disparities in relation to Human Papillomavirus (HPV)-related cancer prevention in three isolated rural Georgia counties; and develop implications for future leadership in rural healthcare research, policy, and practice. Results: The deterministic triad of culture, economy, and geographical location is unique to a rural community, and even if two rural communities experience the same health disparity, each community is likely to have a discretely different composition of cultural, economic, and geographic determinants. Conclusion: The deterministic triad presents a challenge for health policymakers, researchers, and practitioners trying to develop health-related interventions that are equitable, efficacious, and practical in low-resource rural communities. The situation is worsened by the limited opportunities for employment, which leads to greater disparities and creates propagating cultural norms that further reduce access to healthcare and opportunities for sustainable health promotion.